Perception and preference of pharmacy students toward e-learning during the COVID-19 pandemic - Mohammed Mahmood Mohammed; Abeer Abdulhadi Rashid; Ashwaq Najemaldeen Abbas (Wolters Kluwer Medknow Publications, 2023)
This study is designed to evaluate students' knowledge and perceptions about the online learning of pharmacy curricula in Iraq during the COVID-19 quarantine. A descriptive, cross-sectional study involving 278 pharmacy students was done between October 2020 and June 2021. About 42.44% preferred face-face lecturers over other modes of delivery for lectures in the pharmacy curriculum. Most participants preferred both active learning and face-face lectures. The results show that 72.66% of responders chose to stay at home as one of the privileges of e-learning. However, the main barriers that associated with e-learning were lack of patient involvement and some technical issues regarding IT equipment, (74.82%) and (62.23%), respectively. E-learning is seen as a lack of social presence, less social contact, and synchronization of connections. However, e-learning undoubtedly benefits students in several ways. Online learning is an essential podium for students to achieve their studies in periods of crisis.